Attitudes and discourse: spanish practitioners’ and undergraduates’ survey results (2015)
The emergence of English as the international language of communication has increased the attention and concern given its teaching and learning. This survey-based study explores the attitudes of Spanish practitioners and undergraduate students towards English as the vehicular language in the field of medicine and towards Medical Electronic Popularizations as an alternative to medical research articles. The survey results point out that these subjects’ perception of English as the vehicle of communication in the medical field and their conceptualization of medical electronic popularizations are positive. Pedagogical implications can be drawn from this study since it confirms our students’ awareness of the use of English and the new-born genres or communication channels.El papel del inglés como lenguaje internacional de comunicación ha despertado interés en lo que respecta a su enseñanza y aprendizaje. El presente sondeo explora las actitudes de médicos y estudiantes de medicina españoles hacia el inglés como lenguaje vehicular y hacia nuevos géneros emergentes como las popularizaciones médicas difundidas por Internet. Los resultados señalan que estos sujetos tienen una actitud positiva ante ambos; el inglés como lenguaje vehicular y ante estas popularizaciones médicas. Este estudio confirma que ambos grupos asumen la importancia del inglés como herramienta básica de comunicación en el campo de la medicina y del protagonismo de estos géneros electrónicos emergentes.